Emission reduction characteristics of after-treatment system on natural gas engine: Effects of platinum group metal loadings and ratios. (20th May 2021) - Ren, Yedi; Lou, Diming; Tan, Piqiang; Zhang, Yunhua; Sun, Xia
Abstract: In this study, six different three-way catalysts were tested based on the engine bench to investigate the effect of platinum group metal (PGM) loadings and ratios of the catalysts on the transient emission characteristics of a heavy-duty natural gas engine. From the results of this study, NOx are the most important emissions to be considered when optimizing catalyst parameters. PGM ratio can significantly affect the total emissions and change the distribution of peak emissions, while PGM loading showed small impact on total emissions and no effect on peak emissions distribution. The main contribution of higher PGM loading and better PGM ratio were the faster light-off of the after-treatment system and the reduction of peak emissions. With decrease of Rh content and Pt/Pd ratio, NOx, HC, and CO emissions all increased, while NH3 concentration decreased. Pt is indispensable in formula and TWC without Pt content exceeded the regulation limit. For NH3, the average concentration increased in cold-start cycle and decreased in hot-start cycle when PGM loading increased. Slightly reduce the Rh content and increase the Pt/Pd ratio is a feasible route to reduce the cost of the TWC as well as maintain a high efficiency. The findings of this paper provide scientific references to balance cost and performance of TWC on natural gas engine, while achieving engine clean emissions. Graphical abstract: Image 1 Highlights: TWCs of 3 PGM loadings and 4 PGM ratios were tested on engine bench. PGM ratio has significant effect on the distribution of the peak emissions. NOx is the most critical factor when optimizing TWC formula of natural gas engine. Pt content has indispensable effect on NOx emission reduction. Reduce Rh and increase Pt/Pd ratio is feasible to balance the efficiency and cost.